Directing the Solid-State Properties of Phenylene Ethynylenes through Programmable Interactions of Side Chains - Sharber, Seth. (Tufts University. Tisch Library., 2019)
Although π-conjugated organic materials enable the pursuit of attractive new technologies due to their unique properties, programming material function from chemical structure is hindered by the challenge of controlling spatial arrangement of conjugated materials (CMs) in solids, which is integral to bulk properties but driven by weak non-covalent interactions. Rational design requires strategies to direct molecular packing through non-covalent interactions. By taking advantage of underutilized chemical side chains, we direct the solid-state properties in three-ring phenylene ethynylenes (PEs) through stacking interactions between fluoroarenes in side chains and terminal arenes in the chromophore (ArF-ArH interactions). These interactions program a twist into PE backbones, which dictates their fluorescence in solids. Chapter 2 describes how electronic substituents in PEs modulate the dominance of ArF-ArH interactions and thus switch molecular packing, resulting in large fluorescent shifts. Electron-donating substituents strengthen the interaction, and crystal structures reveal twisted, non-aggregated assemblies of PEs. In contrast, electron-withdrawing substituents weaken the interaction, and sufficiently electron-withdrawing groups result in bathochromically shifted solids with planar and/or aggregated PEs in crystal structures. Chapters 3 and 4 investigate how lengths of terminal alkyl chains in PEs tune phase behavior and stimuli-responsive properties. In chapter 3, alkyl chains in aniline-terminated PEs can tune aspects of mechanically induced changes in fluorescence—mechanofluorochromism (MFC). The lengths of terminal aliphatic substituents tune the thermal recovery process in MFC as a result of modifying molecular packing of PEs. In chapter 4, competition between non-covalent interactions enables crystal polymorphism. Weakening ArF-ArH interactions via ester substituents yields polymorphs featuring either programmed twisting or PE aggregation, and alkyl chains can bias competition between these phases, affecting polymorphism, MFC, and crystal-to-crystal transitions of metastable phases. Chapter 5 focuses on fluorinated side chains, where minimal structural changes can broadly switch properties. Regiochemical variations in the fluorine substitution pattern of side chains would not normally be expected to direct packing, but regioisomeric PEs that differ only in the position of a single fluorine in the side chains can show large shifts in fluorescence as well as inversion of the direction of MFC shifts due to switches in the presence or absence of programmed twisting.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Chemistry.; Advisor: Samuel Thomas.; Committee: Clay Bennett, Charlie Sykes, and Mu-Ping Nieh.; Keywords: Chemistry, and Organic chemistry.